Trends in youth cannabis use across cannabis legalization: Data from the COMPASS prospective cohort study - Alexandra M.E. Zuckermann; Katelyn V. Battista; Richard E. Bélanger; Slim Haddad; Alexandra Butler; Mary Jean Costello; Scott T. Leatherdale (Preventive Medicine Reports, 2021)
Canada legalized recreational cannabis use for adults on October 17, 2018 with decision-makers emphasising the need to reduce cannabis use among youth. We sought to characterise trends of youth cannabis use before and after cannabis legalization by relying on a quasi-experimental design evaluating cannabis use among high school students in Alberta, British Columbia, Ontario, and Québec who participated in the COMPASS prospective cohort study. Overall trends in use were examined using a large repeat cross-sectional sample (n = 102,685) at two time points before legalization (16/17 and 17/18 school years) and one after (18/19 school year). Further differential changes in use among students affected by legalization were examined using three sequential four-year longitudinal cohorts (n = 5,400) of students as they progressed through high school. Youth cannabis use remains common with ever-use increasing from 30.5% in 2016/17 to 32.4% in 2018/19. In the repeat cross-sectional sample, the odds of ever use in the year following legalization were 1.05 times those of the preceding year (p = 0.0090). In the longitudinal sample, no significant differences in trends of cannabis use over time were found between cohorts for any of the three use frequency metrics. Therefore, it appears that cannabis legalization has not yet been followed by pronounced changes on youth cannabis use. High prevalence of youth cannabis use in this sample remains a concern. These data suggest that the Cannabis Act has not yet led to the reduction in youth cannabis use envisioned in its public health approach.